2013
DOI: 10.1364/oe.21.00a669
|View full text |Cite
|
Sign up to set email alerts
|

Optical design of transparent metal grids for plasmonic absorption enhancement in ultrathin organic solar cells

Abstract: Transparent metal grid combining with plasmonic absorption enhancement is a promising replacement to indium tin oxide thin films. We numerically demonstrate metal grids in one or two dimension lead to plasmonic absorption enhancements in ultrathin organic solar cells. In this paper, we study optical design of metal grids for plasmonic light trapping and identify different plasmonic modes of the surface plasmon polaritons excited at the interfaces of glass/metal grids, metal grids/active layers, and the localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Typically, when plasmonic electrodes are incorporated into interlayers, the hybrid metallic-interlayer structures serve as both the electron-or hole-selective layer as well as the front transparent electrode. Combined plasmonic interlayer/transparent electrode structures have typically employed 1-D 49,50,[168][169][170] or 2-D 168 gratings. In these cases, since the hybrid plasmonic electrode-interlayer serves as the transparent electrode as well, the devices benefit from both the plasmonic effects (as described in Secs.…”
Section: Plasmonic Interlayersmentioning
confidence: 99%
“…Typically, when plasmonic electrodes are incorporated into interlayers, the hybrid metallic-interlayer structures serve as both the electron-or hole-selective layer as well as the front transparent electrode. Combined plasmonic interlayer/transparent electrode structures have typically employed 1-D 49,50,[168][169][170] or 2-D 168 gratings. In these cases, since the hybrid plasmonic electrode-interlayer serves as the transparent electrode as well, the devices benefit from both the plasmonic effects (as described in Secs.…”
Section: Plasmonic Interlayersmentioning
confidence: 99%
“…13,14 In these studies, thickness of the active layer in OSC devices is too small and optical resonance does not occur within the device. No absorption improvement is observed for TE-polarized light.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Among them, metallic gratings have attracted much attention since the surface plasmon resonance corresponding to the metallic gratings can improve light absorption for transverse-magnetic (TM) polarized light. [9][10][11][12][13][14] However, when transverse-electric (TE) polarized light is illuminated on the metallic grating, previous research has reported that surface plasmon resonance can not be excited and optical absorption is even reduced by high reflection from the metal grating. 13,14 This letter aims to simultaneously improve optical absorption of both TE-polarized and TMpolarized light for OSCs with Ag grating used as the transparent electrode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is accomplished by embedding metallic nanoparticles and nanorods into or near the active layer [4][5][6][7]. Similarly, metallic gratings on the top transport conducting layer [8,9] or on the surface of the back silver electrode [10][11][12] have been employed. In all cases, the excitation of surface plasmonic modes enhances the absorption efficiency.…”
Section: Introductionmentioning
confidence: 99%